Vibration Attenuation of a Nonlinear Oscillator by using the Bound on a system. (October 2017) - Naik, Raghavendra Datta; Mhalsekar, Shridhar D.
Highlights: Lyapunov stability theory is utilized to show boundedness of the solution. The optimal parameters are found by estimating bound on the system. The proposed theory can estimate the parameters of a nonlinear autonomous system to relatively good precision and superior vibration attenuation can be predicted. Abstract: This work examines dynamic optimization of an autonomous oscillator with nonlinearities in stiffness and damping. Lyapunov analysis is utilized to show boundedness of the solution. The ultimate bound on the system is found by using Lyapunov stability criterion. The optimal parameters are found by estimating the bound on the system. The proposed theory can predict the parameters of a nonlinear autonomous system to a relatively good precision and superior vibration attenuation can be predicted.